Two pictures of prominent socialists involved in the 'Lötzener Kettenprozess'. 'Enchained' the members of the 'Braunschweiger Ausschuss', arrested on September 9, 1870 because of the September 5-manifesto, and send shackled to Boyen-prison near Lötzen, where they were joined later on by Jacoby and Becker
Two pictures of prominent socialists involved in the 'Lötzener Kettenprozess'. 'Enchained' the members of the 'Braunschweiger Ausschuss', arrested on September 9, 1870 because of the September 5-manifesto, and send shackled to Boyen-prison near Lötzen, where they were joined later on by Jacoby and Becker.